Analysis and Relevance of Hamka's Praise Thought in The Post-Modern Age - Rahmat Hidayat; Ma Achlami HS; Hasan Mukmin; Rosidi Rosidi; Rini Setiawati (CV. Syntax Corporation Indonesia, 2023)
Delivering da'wah in this post-modern era cannot be separated without leaving the teachings of Islamic law. Hamka is of the opinion that da'wah is a means to make Muslim individuals understand good things and bad things. Hamka offers the concept of da'wah that can be saidcomprehensive. Hamka's thinking is contextual in nature which can be a guide for preachers at that time, the present, and the future. Hamka places da'wah as a very important matter in Islam. The purpose of this study is to analyze and find out the relevance of Hamka's da'wah thoughts in the post-modern eramodern. In conducting this research, the authors used library research, namely research that utilizes or uses library resources to obtain research data. Da'wah in Hamka's thinking is a means of humans and Allah Swt in the form of invitations between humans to do good. Da'wah in Hamka's thinking cannot be separated from the concept of developing Islamic society both in the realm of objectives which both make mad'u or society empowered economically.ideology so that it can make society better than before, in the realm of principles of community development with da'wah which in its implementation there is no element of coercion based on the needs and potential of each, and in its implementation which is followed by all groups. To deal with problems in modern times that can resulting in moral and ethical deviations, Muslims are required to stick to the teachings of their religion which are based on itAl Quran and Sunnah. Basically, Islam does not conflict with modern life, as long as modernity does not conflict with the values ​​of Islamic teachings.